Towards a 21st century health care system: advancing the case for telecare - Karen B. DeSalvo; Christine Petrin (BMC, 2018)
Abstract Telecare is increasingly recognized as an essential tool for a contemporary twenty-first century health care system even though the evidence is still emerging on its effectiveness. The need to find delivery models like telecare that improve both the convenience and value of care is universal, but particularly pressing for countries like the U.S. and Israel who are facing rising costs related to the needs of individuals with multiple complex conditions. This commentary provides highlights of the current state of practice and policy for telecare and the challenges that remain ahead as it is adopted into the mainstream.